Post-transplant cyclophosphamide for graft-versus-host disease prophylaxis in HLA matched sibling or matched unrelated donor transplant for patients with acute leukemia, on behalf of ALWP-EBMT - Annalisa Ruggeri; Myriam Labopin; Andrea Bacigalupo; Boris Afanasyev; Jan J. Cornelissen; Ahmet Elmaagacli; Maija Itälä-Remes; Didier Blaise; Ellen Meijer; Yener Koc; Noel Milpied; Harry C. Schouten; et al. (BIOMED CENTRAL LTD, 2022)
Background: Experience using post-transplant cyclophosphamide (PT-Cy) as graft-versus-host disease (GVHD) prophylaxis in allogeneic stem cell transplantation (HSCT) from matched sibling donors (MSD) or unrelated donors (UD) is limited and with controversial results. The study aim was to evaluate PT-Cy as GVHD prophylaxis post-HSCT from MSD and UD transplants. We analyzed 423 patients with acute leukemia who received PT-Cy alone or in combination with other immunosuppressive (IS) drugs as GVHD prophylaxis. Seventy-eight patients received PT-Cy alone (group 1); 204 received PT-Cy in combination with one IS drug-cyclosporine-A (CSA) or methotrexate (MTX) or mycophenolate-mofetil (MMF) (group 2), while 141 patients received PT-Cy in combination with two IS drugs-CSA + MTX or CSA + MMF (group 3). Transplants were performed from 2007 to 2015 and median follow-up was 20 months.Results: Probability of overall survival (OS) at 2 years was 50, 52.2, and 62.4%, for the three groups, respectively, p = 0.06. In multivariate analysis, in comparison to PT-Cy alone, the addition of two IS drugs was associated with reduced risk of extensive cGVHD (HR 0.25, p = 0.02). Use of bone marrow (BM) and anti-thymocyte globulin were independently associated with reduced risk of extensive cGVHD. Prognostic factors for non-relapse mortality (NRM) were the addition of two IS drugs to PT-Cy (HR 0.35, p = 0.04), diagnosis of AML, disease status at transplant, and patient CMV serology. Factors associated with increased OS were the use of PT-Cy with two IS drugs (HR 0.49, p = 0.02), AML, and disease status at transplant.Conclusion: For GVHD prophylaxis in MSD and UD HSCT, the addition of IS drugs to PT-Cy enhances its effect and reduces the risk of severe cGVHD, reducing mortality and improving survival.